Ανάπτυξη εικονικής πλατφόρμας προσομοίωσης της παραμόρφωσης ανθρώπινου ήπατος με τη χρήση απτικού μέσου - Δούνας, Δημήτρης (Τμήμα Ηλεκτρολόγων Μηχανικών και Μηχανικών Ηλεκτρονικών Υπολογιστών και Πληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The present study aims at investigating the deformation of human tissues under the influence of a force. In this model the human liver was preferred due to its morphology and properties. The modeling was accomplished through the finite-element method, during which a threedimensional model was developed in the high-level computational environment MATLAB and in Robot Operating System (ROS). For the implementation of the finite element model a code was created. The choice of the three-dimensional model fixed points as well as the influence of the force are achieved through Sensable’s Omni Phantom haptic device, where the user initially sets the number and the nodes of the three-dimensional model, which are fixed. Then he selects the node on which he wants to exercise the force. Βy using the haptic mean we are unable to apply force but only displacement, so the straight model is solved in order to find the force in the contact point and then reverse model is solved so we can identify the diplacements of the other nodes. At the end of the program the user is able to observe both the initial and deformed models through the MATLAB GUI of the Virtual Simulator.
Keywords: MATLAB; Robot Operating System; Finite element model; Haptic device; Omni Phantom; Virtual Simulator; Πεπερασμένα στοιχεία; Απτικό μέσο; Γραφική διεπαφής χρήστη